Factors of percieved quality of maritime tourist destination ́s offer : case of Opatija Riviera - Alkier Radnić, Romina (Array, 2020)
The main goal of the paper is to determine underlying dimensions of perceived quality of maritime tourist destination´s offer. Using the purposive sampling technique, data collection was carried out from January to August 2019 in the destinations of Opatija Riviera, yielding a sample of 155 valid responses. To gain better understanding of underlying dimensions of perceived quality of maritime tourist destination´s offer, we, primarily, use exploratory factor analysis. The research findings have revealed that organization of a destination, gastronomic offer, natural resources, traffic infrastructure, destination´s cultural resources, accommodation capacities, attractions and sports activities are the main factors of perceived quality of maritime tourist destination´s offer.